Heavy : A Mother, a Daughter, a Diet--A Memoir - Weiss, Dara-Lynn (New York Random House Publishing Group, 2013)
An expansion of the author's controversial "Up Front" column in Vogue magazine describes her family's efforts to help her clinically obese, seven-year-old daughter to lose weight, recounting how their progress was challenged by judgmental and conflictingdetractors
Keywords: Weiss, Dara-Lynn; Mothers and daughters -- Biography; Overweight children; Obesity in children